Diagnosis of Anorectal Tuberculosis by Polymerase Chain Reaction, GeneXpert And Histopathogenesis in Anal Fistula Patients - Mandal, Prodip Kumar; Chowdhury, Fayem; Ahsan, Md Kamrul; Masud, AKM Al (Sir Salimullah Medical College Journal, 2022)
Background: Association of tuberculosis (TB) with anal fistulas can make its treatment quite difficult. The main challenge is timely detection of TB in anal fistulas and its proper management. There is little data available on diagnosis and management of TB in anal fistulas. Objective: To detect TB in fistula-in-ano patients were analyzed in different methods utilized. Methods: It was a prospective study conducted in Department of Colorectal Surgery, Bangabandhu Sheikh Mujib Medical University and Department of Surgery & Pathology, Sir Salimullah Medical College Mitford Hospital, Dhaka. Total 258 cases were included in this study during the period January 2018 to December 2020.The sampling was done for tissue (fistula tract lining) and pus (when available). The detection rate of various tests to detect TB and prevalence rate of TB in simple vs complex fistulae were studied. Results: This study shows 84.1% were non TB fistula and 15.9% were TB fistula. Majority were male between non TB fistula and TB fistula which was 87.1% and 85.4% respectively. TB fistulas were more complex than non-tuberculous fistulas (68.3% vs 44.2%) respectively. TB was detected in (7.4%) samples tested by PCR-tissue, 23.6% samples tested by PCR-pus, (1.6%) samples tested with HPE-tissue and 0.8% samples tested by GeneXpert. Conclusion: This study shows the detection of TB by polymerase chain-reaction was higher than by histopathology and GeneXpert. Amongst polymerase chain-reaction, pus had a higher detection rate than tissue. TB fistulas were more complex than non-tuberculous fistulas but aggressive diagnosis and meticulous treatment led to comparable overall success rates in both groups. Sir Salimullah Med Coll J 2021; 29(2): 121-123